Intervertebral disc organ culture for the investigation of disc pathology and regeneration – benefits, limitations, and future directions of bioreactors. (3rd July 2020) - Pfannkuche, Judith-Johanna; Guo, Wei; Cui, Shangbin; Ma, Junxuan; Lang, Gernot; Peroglio, Marianna; Richards, R. Geoff; Alini, Mauro; Grad, Sibylle; Li, Zhen
ABSTRACT: Low back pain is the leading cause of disability worldwide and in many patients the source of pain can be attributed to pathological changes within the intervertebral disc (IVD). As present treatment options fail to address the underlying biological problem, novel therapies are currently subject to intense research. The physiologic IVD microenvironment features a highly complex interaction of biochemical and mechanical factors influencing cell metabolism and extracellular matrix turnover and is therefore difficult to simulate for research purposes on IVD pathology. The first whole organ culture models were not able to sufficiently replicate human in vivo conditions as mechanical loading, the predominant way of IVD nutrient supply and waste exchange, remained disregarded. To mimic the unique IVD niche more realistically, whole organ culture bioreactors have been developed, allowing for dynamic loading of IVDs and nutrient exchange. Recent advancements on bioreactor systems have facilitated whole organ culture of various IVDs for extended periods. IVD organ culture bioreactors have the potential to bridge the gap between in vitro and in vivo systems and thus may give valuable insights on IVD pathology and/or potential novel treatment approaches if the respective model is adjusted according to a well-defined research question. In this review, we outline the potential of currently utilized IVD bioreactor systems and present suggestions for further developments to more reliably investigate IVD biology and novel treatment approaches.